2013
DOI: 10.1016/j.ajodo.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maxillary incisor edge asymmetries on the perception of smile esthetics among orthodontists and laypersons

Abstract: The result of this study corroborates the clinical assumption that symmetry between the maxillary central incisors is a paramount goal for esthetic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
132
3
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(158 citation statements)
references
References 20 publications
13
132
3
10
Order By: Relevance
“…The first group was selected because previous studies showed that they are the most sensitive in detecting deviations from the ideal [10,13,16,17], while the latter group was chosen because they are the primary consumers of dental services [15]. Some authors have found that there is a difference between orthodontists and laypeople when evaluating several smile characteristics [1,3,10,14]. On the contrary, our study did not find any statistically significant differences between these two groups.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The first group was selected because previous studies showed that they are the most sensitive in detecting deviations from the ideal [10,13,16,17], while the latter group was chosen because they are the primary consumers of dental services [15]. Some authors have found that there is a difference between orthodontists and laypeople when evaluating several smile characteristics [1,3,10,14]. On the contrary, our study did not find any statistically significant differences between these two groups.…”
Section: Discussioncontrasting
confidence: 69%
“…The interlabial distance was set to 3.5 mm for the woman and 2.5 mm for the man and an incisal step between centrals and laterals of 1.0 mm for the woman and 0.5 mm for the man, and all mandibular teeth were removed. Each image was then condensed to achieve an image with measurements identical to those on the actual patient [1,16].…”
Section: Methodsmentioning
confidence: 99%
“…9 It is believed that not all people are equally sensitive to specific dental aberrations and, accordingly, that orthodontists are the most, general dentists less, and laypersons the least observant of altered dental esthetics. [10][11][12] Previous research dealing with smile esthetics has focused on buccal corridor spaces, 12 anatomy, [14][15][16] smile arcs, 17 maxillary incisor proportions, 18,19 and mandibular crowding. 20 At least 1 earlier study evaluated the perceptions of orthodontists and laypeople with respect to varying degrees of mandibular incisor crowding as measured with Little's irregularity index (LII).…”
mentioning
confidence: 99%
“…Machado 10 , en el 2013, realizó su estudio empleando como modelos las fotografías de dos mujeres, una de rasgos caucásicos y una de rasgos afrodescendientes; realizó la evaluación de una variable distinta (bordes incisales), pero como conclusión, no obtuvo diferencias en cuanto al color de piel de las modelos sometidas a evaluación. En el presente estudio se usó un solo sujeto modelo: mestizo, cuya fotografía y modificaciones fueron sometidas a grupos evaluadores peruanos (ambos grupos).…”
Section: En El 2006 Kokichunclassified